Importancia de las relaciones públicas para instituciones gubernamentales del cantón Babahoyo - Jiménez Delgado, Bella Tatiana (2020)
Very often you hear about Public Relations departments in the government institutions of the Babahoyo canton, but many of the citizens do not know what is the work that is developed within them. That was the main objective of this research, to determine the importance of having a public relations department in the government institutions of the Babahoyo canton. For the development of this project, interviews were conducted with people who have direct links with these departments, thus demonstrating that: the public relations departments are the main axis of the image and dissemination of the information that is generated within government institutions. It is the professionals in charge of this department who, based on their profile and knowledge, seek the appropriate strategies to ensure that the authorities and their work projects for the benefit of the community are publicized and viewed positively. It is up to those in charge of this department that the members of the community observe the work that is carried out with transparency and with the aim that everyone has a better quality of life. With the working method used, it was possible to verify in a particular way the opinion that people have about the importance of having a public relations department in government entities.